Generalized Conversational Implicature in the Slogans of Popular Chocolate Brands - Amanda Arly; Aylanda Hidayati Dwi Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
Slogans are widely used in advertising to stand out and to persuade the audience to purchase the products, especially in the chocolate industry. Rather than using direct persuasion, brands use creative language to craft their slogans, which can lead to misinterpretation. This study applied Levinson’s Generalized Conversational Implicature to identify the principles applied and the meaning implied in the slogans of seventeen chocolate brands. It was found that two slogans applied the quantity principle – one with the scalar implicature and one with the clausal implicature, eleven applied the informativeness principle, and four applied the manner principle. After identifying the principles, this study further analysed the implicatures and found that they could be categorized into three types of persuasion: direct persuasion, persuasion through brand identity and differentiation, and persuasion through emotional connections. These findings confirm that language functions effectively in slogans and allows brands to insert elegant persuasion in their slogans.